Early vs. Late in Aid Partnerships and Implications for Tackling Aid Fragmentation - Emmanuel Frot (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2009)
Development aid donors disburse aid to many developing countries. This paper shows that whether a partnership is established early or late matters significantly for aid quantities. Donor countries allocate larger shares of their aid budgets to recipients that entered early in their portfolios. This effect is large compared to variations due to recipients' income differences, and matters even in the long run. Entry dates are weakly related to GDP per capita, but are influenced strongly by colonial past. On the other hand, colonial relationships explain only a small part of the observed variation in entry dates. These findings imply that donors, while continuously increasing their number of recipients, have allocated smaller aid quantities to new partnerships. This has direct consequences for aid fragmentation, with many donors disbursing small amounts to a recipient. I study a simple reform that eliminates ``small'' partnerships, but leaves unaffected donor aid budgets and developing countries receipts. The reform reshuffles only about 20 percent of all the aid disbursed in a year but drastically reduces fragmentation.
Keywords: F35; O19; 330; Aid; Fragmentation